2017
DOI: 10.1021/jacs.7b07147
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Ability Determines the Activity of Enzyme-Instructed Self-Assembly for Inhibiting Cancer Cells

Abstract: Enzyme-instructed self-assembly (EISA) represents a dynamic continuum of supramolecular nanostructures that selectively inhibits cancer cells via simultaneously targeting multiple hallmark capabilities of cancer, but how to design the small molecules for EISA from the vast molecular space remains an unanswered question. Here we show that the self-assembling ability of small molecules controls the anticancer activity of EISA. Examining the EISA precursor analogues consisting of an N-capped d-tetrapeptide, a pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
110
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 73 publications
(94 reference statements)
0
110
0
1
Order By: Relevance
“…After the synthesis and purification, we found that the peptide Nap‐G D F D F D Y‐CHO was too hydrophobic and could not completely dissolve in aqueous solution by heating or sonication at the concentration of 0.1 wt % (1 mg mL −1 ). Based on previously reported results of using EISA to form hydrogels of hydrophobic peptides, we thus prepared its phosphorylated peptide Nap‐G D F D F D pY‐CHO (Figure A) as a precursor of the possible hydrogelator.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…After the synthesis and purification, we found that the peptide Nap‐G D F D F D Y‐CHO was too hydrophobic and could not completely dissolve in aqueous solution by heating or sonication at the concentration of 0.1 wt % (1 mg mL −1 ). Based on previously reported results of using EISA to form hydrogels of hydrophobic peptides, we thus prepared its phosphorylated peptide Nap‐G D F D F D pY‐CHO (Figure A) as a precursor of the possible hydrogelator.…”
Section: Figurementioning
confidence: 99%
“…The LC‐MS traces indicated that there was about 85 % of the precursor being converted to the Nap‐G D F D F D Y‐CHO at the gelling point (4 h, Figure S13). These observations, in combine with our previous examples, further demonstrated that hydrophobic molecules could form hydrogels via hydrolysis processes. To verify the good stability of CHO‐gel in extreme environments, the peptide Nap‐G D F D F D pY‐COOH with a free carboxylic group was used to prepare a control hydrogel (COOH‐gel) using the EISA process.…”
Section: Figurementioning
confidence: 99%
“…Differentiated by the abnormal activities of certain enzymes in cancer cells compared to normal cells, EISA could selectively occur in or around cancer cells and has shown emerging anticancer activities. [11][12][13][14] By targeting the over-expression of secreted or membrane-bound hydrolases (e.g., alkaline phosphatase, MMPs), the extracellular nanober network could block the mass exchange of metabolites in cancer cells. 15 With additional targeting moieties, such as cholesterol or triphenylphosphine (TPP), cancer-specic EISA could further affect the lipid ras 16 or disrupt the normal function of mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, EISA has demonstrated the unique advantage of overcoming drug-resistance issues, 18 which makes it an emerging anticancer strategy. 14,19 Nevertheless, thus far, most of the established EISA approaches share a common strategy in which the enzyme converts hydrophilic precursors to hydrophobic assembly building blocks (e.g., phosphatase catalyzed dephosphorylation) 13,20 and initiates the subsequent self-assembly in situ. As the inverse process of dephosphorylation, the phosphorylation that is naturally mediated by a kinase usually induces the disassembly process.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The" in vivo self-assembly" strategy, [11] which has attracted tremendous attention in recent years,m ay provide opportunities to meet this challenge.Xuand co-workers have developed nanofibers based on enzyme-instructed self-assembly (EISA) to target cancer cells, [12] overcome multidrug resistance, [13] or induce cell death selectively. [14] However, limited reports confirm the feasibility of this approach in vivo. Polymer-peptide conjugates (PPCs), with long circulation times and good biocompatibility, [15] may provide an ew direction in deep tumor treatment when combined with the in vivo self-assembly strategy.…”
mentioning
confidence: 99%